RESPON BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) PADA PRENURSERY TERHADAP JENIS KOMPOS DAN TAKARAN PUPUK UREA - Sumantri, Adi (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2017)
This study aims to determine and study the response of oil palm seedlings (Elaeis gueneensis Jack) to the type of compost and dosage of urea fertilizer. This research was conducted in the house of researchers in Sukajadi Village, Talang Kelapa Sub-district, Banyuasin District, from February to May 2017. The method used is the Randomized Block Design (RAK) method factorial by 8 combinations of 4 refracting groups with 5 plant samples. The parameters used in this study are sebgai following percentage of seedlings (%), plant height (cm), number of leaves (strands), number of roots (root), root length (cm), wet weight weight (g), and weight Dry trimmed (g). Based on the results of the diversity showed that the compost type treatment had a very significant effect on root length, not significant effect on other variables, the urea fertilizer treatment rate had a very significant effect on all observed variables, the interaction treatment had a very significant effect on the high and wet weight Have no significant effect on other variables.